Metodologias para previs\~ao de receitas tributárias no Brasil - Mário Jorge Mendonça; Geraldo Sandoval Góes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The objective of this study is to perform an econometric modeling exercise of the individual series of taxes aiming to obtain income elasticity and the future projection for each tax. For this, we apply dynamic linear models (MLD) and dynamic factor (MFD), both estimated based on the Bayesian approach. Our sample of taxes accounts for over 90% of the Brazilian tax burden, consisting of monthly data between December 2006 and May 2019. The forecast within the sample is made for the period of one year while the projection out of the sample is from June 2019 to June 2020. The results obtained corroborate the expectation regarding the adequacy of the methodologies used. The exercises for forecast validation showed excellent performance considering the various evaluation criteria. In particular, for most cases, the percentage accumulated error was below 4%; and in some cases the value obtained for this indicator was below 1%.
Keywords: H20; H22; C32; 330; Brazilian gross tax burden; dynamic linear model; dynamic fact